2014
DOI: 10.5539/gjhs.v6n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Report on Maternal Anxiety 16 Months After the Great East Japan Earthquake Disaster: Anxiety Over Radioactivity

Abstract: The Great East Japan Earthquake occurred on March 11, 2011. The tsunami caused extensive damage to the Fukushima Daiichi Nuclear Power Plant, resulting in a level 7 nuclear accident. Among those affected by this combined disaster were many pregnant and parturient women. Sixteen months after the earthquake, we conducted a questionnaire survey on anxiety among 259 women who gave birth around the time of the earthquake in Miyagi Prefecture, one of the affected areas. Participants reported 12 categories of anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
(19 reference statements)
0
22
1
Order By: Relevance
“…The second limitation was that subjects comprised only elderly individuals. A study including mothers with young children for example, may have produced different results [ 27 ]. The third limitation was that only individuals who could walk independently were included.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation was that subjects comprised only elderly individuals. A study including mothers with young children for example, may have produced different results [ 27 ]. The third limitation was that only individuals who could walk independently were included.…”
Section: Discussionmentioning
confidence: 99%
“…Women were more likely to be psychologically distressed among those evacuated after the Fukushima nuclear radiation after the tsunami in 2009 in Japan (Suzuki et al 2015). Pregnant women who were exposed to Fukushima nuclear radiation showed high levels of maternal anxieties about its effect on embryos, children, and food safety among others (Yoshii et al 2014). Varela et al (2008) also note that women's stress levels were marginally higher than those of men after the earthquake in Greece in 1999 (Varela et al 2008).…”
Section: Critical Literature Review and Development Of Conceptual Framentioning
confidence: 99%
“…The Japanese Government gradually expanded the designated evacuation areas without using data from the System for Prediction of Environmental Emergency Dose Information (Hasegawa et al, ). Controversy among experts regarding the risk of the leaked radiation caused confusion and distrust among the Fukushima people (Shimura, Yamaguchi, Terada, Svendsen, & Kunugita, ; Yoshii, Saito, Kikuchi, Ueno, & Sato, ). With a history of atomic bombings in Hiroshima and Nagasaki in 1945, the Japanese people have a fear of radiation exposure and its adverse health effects (Hasegawa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mothers felt anxious about the effects of radiation on their children's health and their future (Ito et al, ; Yoshii et al, ). The Fukushima health management survey demonstrated that women were more concerned about immediate and delayed health effects than men (Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%